2018
DOI: 10.1016/j.cmpb.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Microaneurysm detection using fully convolutional neural networks

Abstract: Performance, simplicity, and robustness of the proposed method demonstrates its suitability for diabetic retinopathy screening applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 28 publications
0
85
0
Order By: Relevance
“…Different CNN structures have been developed to solve image processing, pattern recognition, classification, and other problems. Recently, CNNs have been used for facial recognition (Lawrence, Giles, Ah Chung, & Back, 1997), handwritten character classification (Ciresan, Meier, Gambardella, & Schmidhuber, 2011), visual document analysis (Simard, Steinkraus, & Platt, 2003), face sketch synthesis (Jiao, Zhang, Li, Liu, & Ma, 2018), microaneurysm detection (Chudzik, Majumdar, Calivá, Al-Diri, & Hunter, 2018), fingerprint enhancement (Li, Feng, & Kuo, 2018), the segmentation of glioma tumours in brains (Hussain, Anwar, & Majid, 2018), handwriting recognition (Baldominos, Saez, & Isasi, 2018), granite tile classification (Ferreira & Giraldi, 2017), segmenting the neuroanatomy (Wachinger, Reuter, & Klein, 2018), change detection using heterogeneous optical and radar images (Liu, Gong, Qin, & Zhang, 2018), predicting eye fixations (Liu, Han, Liu, & Li, 2018), improving acoustic source localization in noisy and reverberant conditions (Salvati, Drioli, & Foresti, 2018), chest disease detection (Abiyev & Ma'aitah, 2018), short-term wind speed forecasting (Khodayar, Kaynak, & Khodayar, 2017), natural language processing (Kalchbrenner, Grefenstette, & Blunsom, 2014), and image and video recognition problems (Karpathy et al, 2014) and showed good results.…”
mentioning
confidence: 99%
“…Different CNN structures have been developed to solve image processing, pattern recognition, classification, and other problems. Recently, CNNs have been used for facial recognition (Lawrence, Giles, Ah Chung, & Back, 1997), handwritten character classification (Ciresan, Meier, Gambardella, & Schmidhuber, 2011), visual document analysis (Simard, Steinkraus, & Platt, 2003), face sketch synthesis (Jiao, Zhang, Li, Liu, & Ma, 2018), microaneurysm detection (Chudzik, Majumdar, Calivá, Al-Diri, & Hunter, 2018), fingerprint enhancement (Li, Feng, & Kuo, 2018), the segmentation of glioma tumours in brains (Hussain, Anwar, & Majid, 2018), handwriting recognition (Baldominos, Saez, & Isasi, 2018), granite tile classification (Ferreira & Giraldi, 2017), segmenting the neuroanatomy (Wachinger, Reuter, & Klein, 2018), change detection using heterogeneous optical and radar images (Liu, Gong, Qin, & Zhang, 2018), predicting eye fixations (Liu, Han, Liu, & Li, 2018), improving acoustic source localization in noisy and reverberant conditions (Salvati, Drioli, & Foresti, 2018), chest disease detection (Abiyev & Ma'aitah, 2018), short-term wind speed forecasting (Khodayar, Kaynak, & Khodayar, 2017), natural language processing (Kalchbrenner, Grefenstette, & Blunsom, 2014), and image and video recognition problems (Karpathy et al, 2014) and showed good results.…”
mentioning
confidence: 99%
“…A three-phase MA detection framework is pro-posed by Piotr Chudzik et al [31] by utilizing fully Convolution neural network. Besides how knowledge transfer between the small data set for recognition of MA is shown.…”
Section: H Deep Learning Methodsmentioning
confidence: 99%
“…It can be seen that the proposed method has better performance on MA detection compared to existing algorithms. Especially, as to those using deep learning techniques, the algorithms proposed by Eftekhari et al [8] and Chudzik et al [31] performed very well on FROC score, using two-step CNN and FCN, respectively. It is known that deep learning with CNN for classification has a better performance on accuracy but more computation time for training, requirement of a large number In DIARETDB1 database, MA detection results corresponding to different confidences are shown in different colored circles in Fig.…”
Section: Computation Timementioning
confidence: 99%
“…As deep learning is an emerging computer vision application in medical image processing and proving to be of great help to mankind in machine learning [15], several MA detection methods based on convolutional neural networks (CNN) [8,[29][30][31][32] were proposed. The main limitation of CNN is the requirement of larger training time [15].…”
mentioning
confidence: 99%